2022
DOI: 10.1111/iju.14841
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and focal treatment for metastatic renal cell carcinoma: A literature review

Abstract: Abbreviations & Acronyms AS = active surveillance cCa = corrected calcium CI = confidence interval CN = cytoreductive nephrectomy CNS = central nervous system CR = complete response HR = hazard ratio ICI = immune checkpoint inhibitor IFN-a = interferon alpha IMDC = International Metastatic RCC Database Consortium IPTW = propensity scorebased inverse probability of treatment weight KPS = Karnofsky performance status mRCC = metastatic renal cell carcinoma NLR = neutrophil-tolymphocyte ratio ORR = objective respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
(226 reference statements)
1
11
0
Order By: Relevance
“…25 Another study based on the IMDC database reported that patients with synchronous mRCC who had estimated survival times of less than 12 months may not benefit from CN. 26,27 In this study, the negative impact of r-IF on patient survival was also observed in the subanalysis of patients with synchronous mRCC and similarly for those who underwent CN. The limited number of cases did not allow further investigations to discuss the clinical implications of r-IF in the management of patients with synchronous mRCC, and future studies are required for this purpose.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…25 Another study based on the IMDC database reported that patients with synchronous mRCC who had estimated survival times of less than 12 months may not benefit from CN. 26,27 In this study, the negative impact of r-IF on patient survival was also observed in the subanalysis of patients with synchronous mRCC and similarly for those who underwent CN. The limited number of cases did not allow further investigations to discuss the clinical implications of r-IF in the management of patients with synchronous mRCC, and future studies are required for this purpose.…”
Section: Discussionsupporting
confidence: 67%
“…There have been several controversies regarding the treatment strategy for patients with synchronous mRCC, particularly those related to the indication for CN. [25][26][27][28][29] As the clinical implications of CN have been changing along with the advancement of systemic therapy for mRCC, an immediate CN is currently considered to be a treatment option restricted only to patients with good performance status, few IMDC risk factors, and a limited metastatic burden. 25 Another study based on the IMDC database reported that patients with synchronous mRCC who had estimated survival times of less than 12 months may not benefit from CN.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of cytoreductive nephrectomy (CN) and metastasectomy have changed, however, and in their review article, Naito et al have provided an excellent overview of the evidence on the topic. 2 CN, which historically was supported by randomized trials showing a survival benefit in the cytokine era, has played an important role for patients with mRCC. 3 Nevertheless, based on the recent results from the CARMENA and SURTIME trials, an immediate CN is currently considered to be a treatment option restricted to patients with a good performance status, few International Metastatic Renal Cell Carcinoma Database Consortium risk factors, and a limited metastatic burden.…”
Section: Editorial Commentmentioning
confidence: 99%
“…The clinical implications of cytoreductive nephrectomy (CN) and metastasectomy have changed, however, and in their review article, Naito et al . have provided an excellent overview of the evidence on the topic 2 . CN, which historically was supported by randomized trials showing a survival benefit in the cytokine era, has played an important role for patients with mRCC 3 .…”
mentioning
confidence: 99%
“…For surgical metastasectomy in mRCC, a meta-analysis on 10 studies by Naito and colleagues shows an advantage in OS for patients with complete metastasectomy compared to patients that did not undergo metastasectomy. However, the authors caution, that because all studies were conducted retrospectively, results might be influenced by selection bias ( 13 ). Data on metastasectomy for oligoprogressive disease (OPD) after systemic treatment for mRCC are rare and there are no studies focussing exclusively on surgical treatment of this entity.…”
Section: Introductionmentioning
confidence: 99%